PENGARUH AKSESIBILITAS DAN FASILITAS TERHADAP KEPUASAN WISATAWAN KE BROKEN BEACH DAN ANGEL’S BILLABONG - Clarissa Yohana Natalia; NMO. Karini; NPE. Mahadewi (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2020)
Broken Beach and Angel's Billabong are two popular tourist attractions on West Nusa Penida however the availability of accessibility and existing facilities are still minimal from the standard. The studi to analyse the influence of accessibility and facilities towards tourists satisfaction to Broken Beach and Angel's Billabong in partial and simultaneously. Data collection are observations, questionnaires, interviews, literature studies, and documentation. Determining technique of the respondents is purposive sampling with the number of respondents were 144 respondents. Furthermore, in analysing the data using multiple regression analysis techniques which is processed using IBM Statistics 23 program. Results of this study partially mention that accessibility give positive and significant efffect on the tourists satisfaction with of 2,266 and significant value of 0,025. While facilities give positive and significant effect on the tourists satisfaction with of 3,795 and significant value of 0,000. Simultaneously, concluded that accessibility and facilities give positive and significant effect on the tourists satisfaction which has effect of 0.290 or 29%, while the 71% is described by other variables that do not fit into the framework of this research concept.